Bear the life and times of Augustus Owsley Stanley III - Greenfield, Robert (Thomas Dunne Books, St. Martin's Press, 2016)
Award winning author and biographer Robert Greenfield brings readers the definitive biography of a Grateful Dead legend Augustus Owsley Stanley III, known better by his nickname, Bear. From extensive interviews with Bear and a major Rolling Stone piece, Greenfield brings readers unparalleled access to one of the most important forces in the rise of the counter-culture of the sixties